Properties and Performance of Ultrafine Grained Titanium for Biomedical Applications - Daniel Jogaib Fernandes; Carlos Nelson Elias; Ruslan Zufarovich Valiev (Materials Research, 2015)
The use of materials for biomedical applications has become vital to enhance the quality of life and longevity of human beings. Commercially pure titanium (cpTi) and titanium alloys are the most adequate materials for some biomedical applications, but cpTi and the Ti-6Al-4V alloy (Ti G5) have limitations for biomedical application due to low mechanical strength and the possibility of ion release, respectively. In order to address this problem, commercially pure ultrafine grained titanium (UFG Ti) obtained by severe plastic deformation (SPD) has been suggested as a promising alternative for biomedical applications. This thermomechanical process is able to improve the strength of cpTi and titanium alloys while keeping their excellent biocompatibility. The purpose of this review was to compare the mechanical strength of UFG Ti, cpTi and a Ti G5 alloy. In addition, the biological performance of UFG Ti was also evaluated by in vivo testing. Prodigious improvements were seen in surface topography, wettability and in homogeneity of oxide layer. The overall improvements in microstructure provided by ECAP technique coupled with surface etching resulted in a remarkable performance of cpTi alloy for biomedical applications.